Effect of familial clustering in the genetic screening of 235 French ALS families. Issue 5 (6th January 2021) - Corcia, Philippe; Camu, William; Brulard, Celine; Marouillat, Sylviane; Couratier, Philippe; Camdessanché, Jean-Philippe; Cintas, Pascal; Verschueren, Annie; Soriani, Marie-Helene; Desnuelle, Claude; Fleury, Marie-Céline; Guy, Nathalie; et al.
Abstract : Objectives: To determine whether the familial clustering of amyotrophic lateral sclerosis (ALS) cases and the phenotype of the disease may help identify the pathogenic genes involved. Methods: We conducted a targeted next-generation sequencing analysis on 235 French familial ALS (FALS), unrelated probands to identify mutations in 30 genes linked to the disease. The genealogy, that is, number of cases and generations with ALS, gender, age, site of onset and the duration of the disease were analysed. Results: Regarding the number of generations, 49 pedigrees had only one affected generation, 152 had two affected generations and 34 had at least three affected generations. Among the 149 pedigrees (63.4%) for which a deleterious variant was found, an abnormal G4C2 expansion in C9orf72 was found in 98 cases as well as SOD1, TARBP or FUS mutations in 30, 9 and 7 cases, respectively. Considering pedigrees from the number of generations, abnormal G4C2 expansion in C9orf72 was more frequent in pedigrees with pairs of affected ALS cases, which represented 65.2% of our cohort. SOD1 mutation involved all types of pedigrees. No TARDBP nor FUS mutation was present in monogenerational pedigrees. TARDBP mutation predominated in bigenerational pedigrees with at least three cases and FUS mutation in multigenerational pedigrees with more than seven cases, on average, and with an age of onset younger than 45 years. Conclusion: Our results suggest that familial clustering, phenotypes and genotypes are interconnected in FALS, and thus it might be possible to target the genetic screening from the familial architecture and the phenotype of ALS cases.